ANALISIS DISTRIBUSI PROPORSI PENGGUNA TI BERDASARKAN DATA PENGGUNAAN INTERNET DI INDONESIA - Nadya Revelin Putri; Natasya Priyani; Jadiaman Parhusip (LPPM Politeknik Pratama Kendal, 2024)
This study examines the distribution of internet users in Indonesia, focusing on geographical, demographic, and socio-economic factors affecting the digital divide. Data from APJII (2023), BPS, and other sources reveal that despite over 200 million internet users, significant disparities exist between urban and rural areas. Key factors contributing to this divide include limited infrastructure, high access costs, and low digital literacy. The younger age group (15-35 years) dominates internet usage, while older adults and low-income communities face access barriers. Most internet usage is concentrated on communication and entertainment, with productive activities such as online learning and business transactions remaining underutilized. These findings underscore the need for collaboration among the government, private sector, and communities to address the digital divide through infrastructure development, internet subsidies, and inclusive digital literacy programs.